(untitled) (Nordic Journal of African Studies, 1999)
From men to gods, from aesthetics to art, from textile design to ancestral screens, from the living to the dead, Kalabari idea of perfection is the collage, the composite, the blend. In Kalabari culture, the provocative, the excitable, the lovable, the acceptable or the ideal does not stand apart at the hill top nor dwells in the valley, but adheres at the conjunction of the extremes. This concept of the ideal type principally derives from predilection to borrowing, transformation and reinterpretation of ‘foreign elements.’ This paper is not concerned with Kalabari ability to borrow and adapt, but to show where in their evaluation system they locate the beautiful, the dangerous, the powerful, and the exceptional. My investigations have shown that the position in the evaluation spectrum that indicate excellence, danger or power are often points that are embodiments of differing categories . The admixture category, not the pure, is what is held up to be the high point.